DIRECT BIOLEACHING OF ZINC USING manihot esculenta crantz (cassava) EXTRACT WITHOUT ADDITIVES - Ajibola, Olawale O.; Adebayo, Abdullahi O.; Borisade, Sunday G.; Adegbenro, A. E.; Oloruntoba, D. T.; Olubambi, P. A. (FUDMA JOURNAL OF SCIENCES, 2020)
The advent and development of new technologies that will provide better yields, cleaner and a safer environment is a global challenge for the researchers. Traditional solvents used in extraction of minerals are at many times hazardous thereby constituting threats to the ecology. The work reports the direct bioleaching of zinc sourced from Abakaliki-Ishiagwu complex zinc sulphide ore deposit. The sphalerite ore is predominant in Zn with other associated metals Pb, Cu, Fe, Ni, Sb, As, Cd, Au, V, Co, Ag, K, Al and Ca. It covers the pre extraction processes of mineral comminution (crushing and grinding); separation by froth flotation; and roasting. Agro-cyanide was extracted from cassava plant (Manihot esculenta Crantz) leaves and was used as leachant without any additive.  The result of atomic absorption spectrometry (AAS) analysis of the leached liquor (pregnant solution) shows that lead, copper and iron in addition to Zinc, were obtained from the leached ore roast at 149.25 ppm (Zn), 79.25 ppm (Pb), 0.25 ppm (Cu) and 4.25 ppm (Fe) extraction after 21 days. Elongated contact of ZnO ore is not encouraging for Zn extraction as there is a decline in the quantity of Zn, Fe and Cu as the leaching time (days) increases. The mechanism of the Leach next faction is yet to be fully ascertained, hence the need for further work in the area.
Keywords: direct bioleaching, zinc ore, Manihot esculenta Crantz, leach extraction